The Analysis Of Factors Related To The Use Of Post-Placenta Iud For Mothers Who Have Just Delivered A Baby In Yogyakarta - Susiana Sariyati; Fatimah Fatimah (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
Yogyakarta has the smallest increase of the number of new family planning participants across the Special Region of Yogyakarta, i.e. 11.18%. In Gunung kidul, it’s 11.93%, Sleman 11.98%, Bantul 12.72%, Kulon progo 13.28%. The purpose of this study was determining factors related with post placenta IUD  usage by women in labor in Yogyakarta. This was an analytical observational research with cross sectional design. Total sample in this study was 84 respondents collected using Accidental Sampling. The independent variables in this study were age, parity, education, occupation, family planning history, husband’s support. The dependent variable was the usage of post placenta IUD contraception. The analysis used bivariate test, i.e. Chi Square, while multivariate test used regresi logistic analysis. Age as p value of 0.1, parity 0.055, mother’s education 0.381, mother’s occupation 0,400, family planning history 0.062 and husband’s support 0.0001 on the usage of post placenta IUD. Multivariate analysis showed that the strongest relation was with husband’s support. There was no relation between age, parity, educaiton, mother’s occupaiton, family planning history and the usage of post placenta IUD, but there was relation between husband’s support and the usage of post placenta IUD.